2016
DOI: 10.1111/desc.12476
|View full text |Cite
|
Sign up to set email alerts
|

Linking executive function skills and physiological challenge response: Piecewise growth curve modeling

Abstract: This study employed piecewise growth curve modeling to examine how children's executive function (EF) skills relate to different components of children's physiological response trajectory - initial arousal, reactivity, and recovery. The sample included 102 ethnically diverse kindergarteners, whose EF skills were measured using standard tasks and observer ratings. Physiological response was measured via changes in respiratory sinus arrhythmia (RSA) in response to a laboratory socio-cognitive challenge. Children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 86 publications
(135 reference statements)
7
45
0
Order By: Relevance
“…Indeed, more rapid parasympathetic recovery has been specifically associated with better aspects of self-regulation, including better executive function abilities (Obradovic & Finch, 2016) and better behavioral strategies for coping with a later delay of gratification challenge (Santucci et al, 2008). In a previous report on this same sample, we found that preschoolers' greater sympathetic recovery (lengthening PEP) following anger induction was associated with mothers' reports of better overall emotion regulation (Kahle et al, 2016).…”
Section: Adding Complexity: Dynamic Change and Recoverymentioning
confidence: 56%
See 1 more Smart Citation
“…Indeed, more rapid parasympathetic recovery has been specifically associated with better aspects of self-regulation, including better executive function abilities (Obradovic & Finch, 2016) and better behavioral strategies for coping with a later delay of gratification challenge (Santucci et al, 2008). In a previous report on this same sample, we found that preschoolers' greater sympathetic recovery (lengthening PEP) following anger induction was associated with mothers' reports of better overall emotion regulation (Kahle et al, 2016).…”
Section: Adding Complexity: Dynamic Change and Recoverymentioning
confidence: 56%
“…Recently, a few developmental studies have used latent growth curve models to show that nonlinear patterns of RSA change best characterize responding across an emotional task (Brooker & Buss, 2010;Miller et al, 2013;Obradovic & Finch, 2016).…”
Section: Adding Complexity: Dynamic Change and Recoverymentioning
confidence: 99%
“…Studies of PEP recovery are notably absent from the current literature. RSA studies generally support positive associations between optimal parasympathetic regulation and positive adjustment outcomes (Berntson, Cacioppo, & Quigley, ; Butler, Wilhelm, & Gross, ; Calkins et al, ; Cipriano, Skowron, & Gatzke‐Kopp, ; Gentzler, Santucci, Kovacs, & Fox, ), and recent studies of RSA recovery suggest that the capacity to return toward resting levels following a stressor is related to fewer behavior problems and positive executive functioning (Cui et al, ; Kahle et al, ; Miller et al, ; Obradović & Finch, ; Rudd et al, ).…”
Section: Introductionmentioning
confidence: 95%
“…Results are inconsistent in two aspects (see Graziano & Derefinko, 2013;Obradović & Finch, 2016Porges, 2007 Greater RSA withdrawal in response to various laboratory challenges has been associated with increased sustained attention, engagement during challenge tasks, on-task behaviors in the classroom, and cognitive functioning, as well as more adaptive emotion regulation strategies (Blair & Peters, 2003;Calkins, Blandon, Williford, & Keane, 2007;Calkins & Keane, 2004;Doussard-Roosevelt, Montgomery, & Porges, 2003;Staton et al, 2009;Suess et al, 1994). Similarly, Becker and colleagues reported that better performance on an EF task was associated with greater RSA withdrawal among elementary school students (Becker et al, 2012).…”
Section: Are the Largest Phasic (Reactive) Changes Observed At Intermmentioning
confidence: 99%
“…Obradovic & Finch suggested than one reason for these inconsistent results may be that RSA studies tend to study change over relatively long time-scales (minutes) (Obradović & Finch, 2016). This may mean that a number of different subcomponent processes (initial withdrawal, maintenance of change, recovery) are all included in the measure of RSA withdrawal (Porges, 2007).…”
Section: Are the Largest Phasic (Reactive) Changes Observed At Intermmentioning
confidence: 99%